The Influence Of Empowering Leadership On Innovative Work Behavior With Mediator Self-Efficacy And Moderator Role Clarity At PT. XYZ - Vania Intar Zerlinda; Praptini Yulianti (International Publisher, 2023)
This study aims to see the effect of empowering leadership on innovative work behavior with self-efficacy as a mediating variable and clarity of role as moderator at PT. XYZ. PT. XYZ is a food and beverage plastic packaging product manufacturing company located in Krian, Sidoarjo, East Java. The population and sample in this study were PT. XYZ’s 102 permanent employees consists of 5 employees in the Marketing Department, 41 employees in the R&D Department, and 56 employees in the Production Department. Sampling in this study by conducting a census that took the entire population. This research measurement technique uses Partial Least Square (SmartPLS) software version 3.0. The results of this study indicate that empowering leadership has a positive and significant effect on self-efficacy, self-efficacy has a positive and significant effect on innovative work behavior, empowering leadership has a positive and significant effect on innovative work behavior, role clarity positively and significantly moderates the effect of empowering leadership on self-efficacy, and self-efficacy can mediate positively and significantly the effect of empowering leadership on innovative work behavior.